Are High Frequency Oscillations in Scalp EEG Related to Age? - Windhager, Philipp Franz; Marcu, Adrian V.; Trinka, Eugen; Bathke, Arne; Höller, Yvonne (Frontiers in Neurology, 2022)
Background: High-frequency oscillations (HFO) have received much attention in recent years, particularly in the clinical context. In addition to their application as a marker for pathological changes in patients with epilepsy, HFO have also been brought into context with several physiological mechanisms. Furthermore, recent studies reported a relation between HFO rate and age in invasive EEG recordings. The present study aimed to investigate whether this relation can be replicated in scalp-EEG. Methods: We recorded high-density EEG from 11 epilepsy patients at rest as well as during motor performance. Manual detection of HFO was performed by two independent raters following a standardized protocol. Patients were grouped by age into younger (< 25 years) and older (>50 years) participants. Results: No significant difference of HFO-rates was found between groups [U = 10.5, p = .429, r = .3.]. Conclusions: Lack of replicability of the age effect of HFO may be due to the local propagation patterns of age-related HFO occurring in deep structures. However, limitations such as small sample size, decreased signal-to-noise ratio as compared to invasive recordings, as well as HFO-mimicking artefacts must be considered.